Detecção, seleção de habitat, ocupação e densidade de aves em risco de extinção na Mata Atlântica do Nordeste. - Lima, Diego Mendes (2024)
Bird vocal activity can be adjusted seasonally due to changes in environmental conditions and interactions. It is important to identify and characterize patterns for threatened and rare species. This knowledge can be applied to determine the optimal period for scheduling individual species counts. Identifying the main bird detection window allows you to maximize records to estimate population density, understand the mechanisms that drive habitat selection and occupancy. This information supports understanding which habitat variations are important for species persistence, spatial behavior patterns and supports conservation measures aimed at improving habitat quality. We investigated how variation in bird species detection varies, providing the first population estimates, and identified which habitat-associated factors can influence the occupancy of threatened taxa, in tropical forest fragments in the Northeast Atlantic Forest, one of the most threatened areas of an important biodiversity hotspot. The data was collected over the course of a year, where two trained observers walked transects within the Guaribas Biological Reserve. As a result of this investigation, we identified the best bird detection window to outline the data collection period for population estimates, habitat selection and probability of occupancy, in the period between September 2022 and February 2023, in the Private National Heritage Reserve Gargaú. The negative finding with the forecast, where the detection hides two months before the start of the rainy season, which occurs between February and June. Some species are blocked throughout the year, others are blocked more during the drier period and others at the beginning of the rainy period. Even with this variation, the joint detection of these species was frequent during the dry period and the beginning of the rainy season. The probability of species occupancy was influenced differently, some effects of elements of the phytosociological structure, such as tree height and tree density, others are associated with areas far from the edge and close to rivers and streams in the interior of the forest, a another had its occupancy opportunity associated with points with shorter trees and, finally, we found a positive relationship between the occupancy of one of the species and humidity inside the forest. We also obtained estimates that will result in different population densities of the following taxa: Xiphorhynchus atlanticus (0.03 ind/ha), Platyrinchus mystaceus niveigularis (0.03 ind/ha), Momotus momota marcgravianus (0.04 ind/ha), Automolus lammi (0.04 ind/ha), Pyriglena pernambucensis (0.05 ind/ha), Xenops minutus alagoanus (0.09 ind/ha). The recorded population density estimates are considered low when compared to another common and non-threatened species in the area, Chiroxiphia pareola (0.33 ind/ha). We suggest that conservation measures on a local scale are mandatory, such as: 1) the planning of seedlings of native and late-stage species within the forest patch, 2) the connection with restoration between fragments, prioritizing locations with watercourses between them; 3) creation of policies and practices for ecological corridors and mosaics; 4) environmental education programs and incorporation of bird watching into an official tourism agenda with the participation of local agents. Such measures together will mitigate the effects of forest fragmentation, allowing the movement of species and the maintenance of biological diversity.